Relasi Agama, Magi Dan Sains Dalam Pentas Politik: Studi Kasus Bunda - Sang Penasehat Spiritual - Hadisaputra, Hadisaputra - (ETNOSIA : Jurnal Etnografi Indonesia, 2016)
Abstract Modern political institutions that glorifies scientific approaches still open a space for metaphysical ones. In a political competition, science institutionalize itself through political survey and consultant, and metaphysical aspect ispersonified by spiritual counselors.This article focuses on the practices of a political spiritual councelor in South Sulawesi, named Bunda. Thesuccessful of Bunda in her practice as a spiritual counselor in the modern era cannot be separated from her ability to to integrate between religion, magi and science. This is performed by combining between the aspects of religion and magi, such as zikir ritual (zikir mappateppe’, zikir hajat, and zikir ‘sapu mata’), animal sacrificing, and employing Majelis Zikir and orphasn for the zikir; and science aspect can be seen from the zikir package with measurable operational costs which can be varied depending on the social status of the candidate and the number of votes needed.The costs of zikir package vary, and each has its own consequencewhich is informed to candidate in advance. Key Words: spiritual councelor, candidate, zikir, magi, science, vote, religion.